Investigação de alterações nos elementos do sistema responsivo a estrógenos e suas possíveis correlações funcionais nas vias genitais masculinas do morcego-das-frutas Artibeus lituratus, durante o ciclo reprodutivo anual - Regiana Lucia de Oliveira (2013)
The efferent ductules (ED) and epididymis (EP) play essential roles which guarantee sperm viability and, thus, male fertility. Among the roles played by these organs, is the transepithelial water and solute transport, which involves aquaporins (AQPs). The reabsorptive function can be modulated by estrogens, which act via receptors ER and ER. Furthermore, it is known that estrogens via ER and ER, participate in the regulation of proliferation and apoptosis, ER being considered a proliferative factor and ER considered a pro-apoptotic factor. The ED are the main targets for estrogens, being ER detected in high levels in all species studied to date. On the other hand, presence of ER in the EP iscontroversial, as it is the presence of aromatase, the enzyme responsible for the conversion of androgens into estrogens. Previous studies show that the big fruit-eating bat Artibeus lituratus present seasonal variation in the testis estrogen- and androgen-responsive system, making it agood model for steroid function studies. Therefore, the present study aimed to investigate the expression of the components of the estrogen-responsive system (aromatase, ER, ER and tissue estradiol levels) in the genital tract of A. lituratus during regressive and reproductiveperiods, as well as their functional correlation with apoptosis, cell proliferation and fluid reabsorption through AQP1 and AQP9. For comparison, testosterone levels and its receptors (AR) have also been studied. Results showed that ER levels vary during the annualreproductive cycle, being higher at the regressive period. This increase parallels that of cell proliferation index, corroborating the proliferative role of ER. The aromatase was detected in ED and EP throughout the reproductive cycle of the species, without seasonal variation asobserved for ER and AR. AQP1 and AQP9 showed cell- and region-specific expression. AQP1 is constitutively expressed in the ED and spermatids, whereas AQP9 expression showed seasonal variation, being expressed only in the EP. No correlation was found betweenAQP9 expression and androgen or estrogen levels, although a crescent correlation with sperm concentration was observed towards the cauda epididymidis. Based on these data, we conclude that the estrogen-responsive system, acting via ER, may play a role in tissuehomeostasis, preparing the genital tract for sexual recrudescence, although its involvement with AQP1 and AQP9 regulation has not been evidenced.